Pals1a and aPKCλ are not essential for Schwann cell migration, division or myelination in zebrafish. Issue 1 (28th November 2022) - Boueid, Marie‐José; Mikdache, Aya; Lesport, Emilie; Delespierre, Brigitte; Loisel‐Duwattez, Julien; Degerny, Cindy; Tawk, Marcel
Abstract: Background: Schwann cells (SCs) are specialized glial cells of the peripheral nervous system that produce myelin and promote fast action potential propagation. In order to myelinate, SCs engage in a series of events that include migration and division along axons, followed by extensive cytoskeletal rearrangements that ensure axonal ensheathment and myelination. SCs are polarized and extend their processes along an abaxonal‐adaxonal axis. Here, we investigate the role of the apical polarity proteins, Pals1a, and aPKCλ, in SC behavior during zebrafish development. Results: We analyzed zebrafish nok and has mutants deficient for pals1a and aPKCλ function respectively. Using live imaging, transmission electron microscopy and whole mount immunostaining, we show that SCs can migrate and divide appropriately, exhibit normal radial sorting, express myelin markers and ensheath axons on time in has and nok mutants. Conclusions: Pals1a and aPKCλ are not essential for SC migration, division or myelination in zebrafish. Key Findings: Schwann cells are specialized myelinating cells of the peripheral nervous system. In this paper, we use live imaging, genetic, transmission electron microscopy and whole mount immunostaining to conduct a thorough analysis of the role of the two canonical polarity proteins Pals1 and aPKC in the development of Schwann cells in zebrafish. This study provides evidence that the canonical polarity proteins tested so far are not required for Schwann cell development in zebrafish underscoring strong differences between mice and zebrafish peripheral glial polarity. This strongly suggests, for the first time, that Schwann cell polarity is established differently in zebrafish and that the abaxonal‐adaxonal axis is independent of canonical polarity proteins. This highlights a novel example of how polarity might differ between cells (epithelial vs glial) and species (zebrafish vs mice).